Steamboat GOV. PINGREE navigating the Yukon River, Yukon Territory, approximately 1898. - Hegg, Eric A., 1867-1948 (1898)
Thirty Mile River is the stretch of the Yukon River between lower Lake LaBerge and the Hootalinqua or Teslin River. Caption on image: "Gov. Pingree. Thirty Mile River" Original image in Hegg Album 16, page 15. Original photograph by Eric A. Hegg B310; copied by Webster and Stevens 256.A.